2019
DOI: 10.3390/app9091862
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Lignocellulosic Biomass by Selective Precipitation from Ionic Liquid Dissolution

Abstract: We propose the treatment of barley straw with 1-ethyl-3-methylimidazolium acetate [EMIMAcO] ionic liquids (ILs) and subsequent precipitation with antisolvent mixtures, thus allowing the separation of the sugar-rich fractions (cellulose and hemicellulose) from the lignin fraction. For this purpose, different concentration ranges of acetone:water antisolvent mixtures were studied. In all cases, a high recovery percentage and a high and effective separation of fractions was achieved for 1:1 acetone:water. The fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…As a result, the solute is precipitated, and the solvent is dissolved in the antisolvent (Sun et al 2007). Cellulose separation can be accomplished by this phenomenon and is called "regeneration" (Lara-Serrano et al 2019). Compressed CO2, ethanol, and water are some known antisolvents (Sun et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the solute is precipitated, and the solvent is dissolved in the antisolvent (Sun et al 2007). Cellulose separation can be accomplished by this phenomenon and is called "regeneration" (Lara-Serrano et al 2019). Compressed CO2, ethanol, and water are some known antisolvents (Sun et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a typical pretreatment, 0.5 g of wheat straw was dissolved in 9.5 g of [EMIM]OAc, which had been previously heated at 105 • C under mechanical stirring (500 rpm). The reactor was stoppered, and the mixture was maintained at 105 • C under vigorous mechanical stirring (950 rpm) for 25 min, according to a previous study [6]. A viscous dark brown suspension was obtained.…”
Section: Wheat Straw Fragmentationmentioning
confidence: 99%
“…After fractioning its main components, e.g., cellulose, hemicellulose and lignin, biomass can be converted into a wide variety of industrial products, such as biofuels, biomaterials, cellulose pulps, cellulose nanofibers, oligosaccharides and a large number of by-products, in addition to lignin derivatives.Numerous studies have shown ionic liquids (ILs) to be effective at solubilizing lignocellulosic biomass, allowing for subsequent regeneration by precipitation with anti-solvents. Depending on the anti-solvent used, it is possible to achieve selective precipitation and separate the lignocellulosic biomass into its main components [6][7][8][9][10][11][12][13][14]. Among the most commonly employed ILs, 1-ethyl-3-methylimidazolium acetate ([EMIM]OAc) holds a privileged position due to its physico-chemical properties.The acid hydrolysis of the polysaccharide fractions of lignocellulosic biomass, which leads to monosaccharides that can be converted into fine chemicals or platform molecules used for industrial applications, can be performed in the presence of enzymes, homogeneous catalysts or heterogeneous catalysts [15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The major components account for more than 80 % of the total dry weight of lignocellulose. [3,4] As can be seen in Table 1, [5][6][7][8][9][10][11][12][13][14][15][16] different species of LCB significantly differ in the amount of the major components. Dry LCBs generally have a carbon content of 50 %, lower than that of coal (75-90 %), and an oxygen content of 45 %, higher than that of coal (< 20 %).…”
Section: Introductionmentioning
confidence: 99%